Consolidation of the activities of regulatory institutions while implementing e-government solutions - Davidavičienė, Vida; Raudeliūnienė, Jurgita; Vengrienė, Elena; Jakubavičius, Artūras (Journal of Business Economics and Management, 2018)
In the context of globalization, information technology development and transformation not only the needs of the society are changing, structural changes are taking place in the management of the activities of the regulatory institutions as well, because their main function is to meet the changing needs of society. While this process is happening, it becomes difficult to balance activities of the regulatory institutions with the needs of the society and business. This is why optimization of the regulatory institutions functions is one the European Union᾽s priorities. One of the most efficient ways to increase the quality of public services, reduce expenses, encourage cooperation between institutions and make decision making process more efficiently is to create an evaluation system that allows assessment of the efficiency of the consolidation of regulatory institutions functions during the implementation of e-government. In order to solve issues, the analysis of scientific literature, multiple criteria and expert evaluation were applied. The proposed system for evaluation of the consolidation of the activities of the regulatory institutions while implementing solutions of e-government allows complete assessment of the factors and criteria, identification of drawbacks of the process and also enables to create decisions for solutions of the problems.